Pioneers vs. Whittier College Saturday, Sept. 19, 1970 - California State College, Hayward Athletics:::::: (1970)
Program for the September 19, 1970 football game between the California State College, Hayward Pioneers and Whittier College. Includes football schedule, team rosters and probable starting lineups, photographs of CSCH players and coaches, schedules for other CSCH sports, and the CSCH alma mater.